Influence of the Framing Effect, Anchoring Effect, and Knowledge on Consumers’ Attitude and Purchase Intention of Organic Food - Shan, Lijie; Diao, Haimeng; Wu, Linhai (Frontiers in Psychology, 2020)
This article explores consumers’ attitude toward and purchase intention of organic food regarding the influence of the framing effect and anchoring effect and the role of knowledge. Our findings suggest that whether message framing describes the benefits of buying organic food or the loss resulting from a failure to buy organic food, significantly influences consumers’ attitude and purchase intention. In addition, presenting an anchor price in advertisements also significantly influences consumers’ judgment. These results indicate that a negatively framed message induces a more favorable attitude and purchase intention than a positively framed message, a low anchor price is more favorable than a high one, and the interaction effect of framing and anchoring is not significant at the 1% level. Finally, consumers with less organic food knowledge are more susceptible to framing and anchoring effects. These results provide suggestions for appropriate message framing and price anchoring to enhance consumption within the organic industry.